Genetic composition of queen conch (Lobatus gigas) population on Pedro Bank, Jamaica and its use in fisheries management - Blythe-Mallett, Azra; Aiken, Karl A.; Segura-Garcia, Iris; Truelove, Nathan K.; Webber, Mona K.; Roye, Marcia E.; Box, Stephen J. (The University of the West Indies, Mona Campus, Jamaica, 2021)
Two hundred and eight samples were collected across the entire Pedro Bank and were genetically characterized using nine polymorphic microsatellite loci.
Keywords: Pedro Bank; Lobatus gigas; queen conch; microsatellite genetic structure; ecosystem based management